Power Transmission of UHF Passive Embedded RFID in Tires - Shengbo Hu; Bing Si; Heng Shu; Jinrong Mo (International Journal of Antennas and Propagation)
UHF passive RFID tags embedded in tires have a deep impact on tire life cycle management and tire monitoring. In this work, we present the power transmission of UHF passive embedded RFID in tires. In UHF passive embedded RFID systems in tires, the bidirectional radio link between reader and tags goes through air and tires. The total path loss contains reflection loss at tire-air boundaries and attenuation loss in the tires. The power transmission is based on the permittivity of tires and tire-air boundary conditions. We give an OCP method for measuring the permittivity of tires. By analyzing the radio link for UHF passive RFID, we establish a model of wave propagation of UHF embedded RFID in tires and make numerical analyses. Numerical analyses show that the error of the OCP methods for measuring the permittivity of tires is small, the parallel polarization and normal incidence of wave are chosen for improving the performance of the UHF embedded RFID in tires, and distance is chosen to keep power transmission function from locating valley.